Comparative Study of the Form of Kings’ Cap in the Safavid and Qajar Eras - A. Sheikhi (Jilvah-i hunar, 2019)
The crown in Iran has always been a symbol of the power and glory of the kingdom. The crown has historically been one of the most prominent symbols of the greatness and power of kings, which are authentic documents of the historical facts of any period or king. In designing the crown and displaying its grandeur and beauty, the artists have made great efforts because this was the special order of the court. It is important to note that communication with Western society from the late Safavid Era has varied the court's tastes. The main purpose of this article is to investigate the form of the crowns of the Safavid and Qajar kings. The question to ask is how well the form and ornamentation of the crowns during these periods has gone. The crown of kings has been described in numerous documents that this paper has investigated the murals, paintings and coins of Safavid and Qajar Eras. Studying the evolution of the crown in Iranian Art History and examining its form as a symbol of the greatness of necessity is a step toward identifying an area of fine art in Iran and beginning to study the other aspects of this courtier element. The crown has taken many forms in Iran's historical course. This article examines the form of the Safavid and Qajar crowns and caps.  In addition to majestic crown, the works included a turbaned crown with a conventional and ensign crown with feather, which symbolizes serenity and beauty. The ancient crown continued in the Qajar era but with a different appearance and at the end of the Qajar with a different form. If attention to the congressional crown is evident in the first half of the Qajar rule, but beside it are capss with round tapered ornamentation in the Fath Ali Shah period. In the middle of the Qajar, it became cut and relatively tall cones adorned with feathers. Eventually, the caps became a simple shape and adorned with stone or a pair of pigeon tails. What is possible in this course is that according to the society of that time and the type of cover, crown and cap that has been deformed, in this respect, external communications from the early Safavid Period and especially from the mid-Qajar Era should be considered. The purpose is to identify the form of the crown and cap of the Safavid and Qajar kings. Therefore, the research seeks to make what do the form and decorations of the crown and cap of the Safavid kings and Qajar with regard to the resources and documents of the remnants? The research approach is qualitative and the research method is descriptive, historical and comparative. Findings show that the crown during the Safavid Period and Qajar Period is influenced by its temporal characteristics, although it tends to preserve ancient forms in Iran. The ancient crown of Iran has a framed, angular and turfed line with its effect on the Safavid Era. In the Qajar Era, crowns are also seen with elliptical, conical and cylindrical shapes and angular lines. The continuity of the shape and form of the Iranian ancient crown is evident in the paintings of the Safavid Period, although slight variation can be seen in the crown, but its overall form has continued. The Qajar period has had widespread changes in various areas. In this period, you can divide the crown and cap of kings into five categories. The first category is the continuation of the ancient crown of Iran. The second and third group is a simple hat on the head of Fath Ali Shah and Abbas Mirza, which is embroidered with pearls and jewelry. The fourth bunch of crowns is a cone that is adorned with baguettes. The fifth category is very simple, and their decorations are unique to a feather front of a cylindrical short hat. In this regard, the type of interactions with the West and the journeys of the Qajar kings to Europe have certainly been effective.